Implementasi dan Tantangan Pendidikan Vokasi Siswa Berkebutuhan Khusus - Ardiani, Rahma; Yoenanto, Nono Hery (JPI (Jurnal Pendidikan Inklusi), 2023)
The implementation of vocational classes is necessary so that student with special needs canprepare for the job competition. Trough vocational classes, student can improve their skill whichsupport a field of work. The success of vocational classes requires family social support, teachers,experts, schools, and external participants. The aim of this research is to describe theimplementation of vocational classes that have been applied to student who has special needs.The research method is narrative literature review. The results explain vocational class programwhich packaged into a career guidance, which contains pre-vocational, vocational, and postvocational. Types of vocational classes include culinary, salon, horticulture, sewing, nail artgradation, barbering, making ceramics, garden lighting, water mills, laundry, cleaning service,hydroponics, drawing, and colouring. Obstacles that arise are low student motivation, limitedschool funding, and inadequate tools. The solution can be proposed is career guidance invocatonal education. Family social support and financial capabilities are needed for the successof vocational education.Keywords: Students with Special Needs, Vocational Education